(untitled) (Swiss Medical Weekly, 2012)
The real utilisation scenario of non-invasive ventilation (NIV) in Swiss ICUs has never been reported. Using a survey methodology, we developed a questionnaire sent to the directors of the 79 adult ICUs to identify the perceived pattern of NIV utilisation. We obtained a response rate of 62%. The overall utilisation rate for NIV was 26% of all mechanical ventilations, but we found significant differences in the utilisation rates among different linguistic areas, ranging from 20% in the German part to 48% in the French part (p <0.01). NIV was mainly indicated for the acute exacerbations of COPD (AeCOPD), acute cardiogenic pulmonary edema (ACPE) and acute respiratory failure (ARF) in selected do-not-intubate patients. In ACPE, CPAP was much less used than bi-level ventilation and was still applied in AeCOPD. The first line interface was a facial mask (81%) and the preferred type of ventilator was an ICU machine with an NIV module (69%). The perceived use of NIV is generally high in Switzerland, but regional variations are remarkable. The indications of NIV use are in accordance with international guidelines. A high percentage of units consider selected do-not-intubate conditions as an important additional indication.